PENGARUH KELAS SOSIAL DAN GAYA HIDUP TERHADAP PERILAKU KONSUMEN PADA KONSUMEN PT MATAHARI DEPARTMENT STORE TBK MALANG - Hasan, Fitriyah; Farida, Lailatul (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This stdy aims to determine the effect of social class and lifestyle on consumen behavior to consumers PT. Matahari Department Store Tbk. Malang. The research method used in this study is a quantitative research method. The sample used was 100 respondents (20 question items x5) referring to the Malhotra theory and the sample in this study were consumers who have made purchases at PT. Matahari Department Store Tbk. Malang. That test was carried out using the Statistical Package for the Social Sciences (SPSS). The sampling techniqque in this study used a Probability Sampling technique. The results of this study indicate that the effect of social class on costumen behavior hasn’t significant but lifestyle has significant effect on costumen behavior.